The American ruling class : [videorecording (DVD)] : a dramatic-documentary-musical - Kirby, John; Burwell, Caton; Cantagallo, Paul; Silver-Greenberg, Jessica (Lorber HT Digital, 2007)
Is there an American ruling class, and if so, how do you join? Two hapless Yale grads embark on a star-studded journey of meetings with America's establishment to unearth some uncomfortable answers and find out the truth about what the future really holds for them. A dramatic, musical, documentary satire on class in America that attempts to answer the question "Who rules America?".